2018
DOI: 10.1039/c8cc03446j
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences between toxic and nontoxic HypF-N oligomers

Abstract: We have studied two misfolded oligomeric forms of the protein HypF-N, which show similar morphologies but very different toxicities. We measured over 80 intermolecular distance-dependent parameters for each oligomer type using FRET, in conjunction with solution- and solid-state NMR and other biophysical techniques. The results indicate that the formation of a highly organised hydrogen bonded core in the toxic oligomers results in the exposure of a larger number of hydrophobic residues than in the nontoxic spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(79 citation statements)
references
References 16 publications
8
71
0
Order By: Relevance
“…31 A 5-μl drop of RT-QuIC product was deposited onto a gold mirror support (ME1S-M01; Thorlabs, Inc., Newton, NJ), followed by air drying for 20 minutes and acquisition of Raman spectra from the outer ring of the dried drop. Backscattered light was collected by a 100× microscope objective with 0.9NA, which generates a 1-μm laser beam waist and a laser power at the sample of 40 mW.…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…31 A 5-μl drop of RT-QuIC product was deposited onto a gold mirror support (ME1S-M01; Thorlabs, Inc., Newton, NJ), followed by air drying for 20 minutes and acquisition of Raman spectra from the outer ring of the dried drop. Backscattered light was collected by a 100× microscope objective with 0.9NA, which generates a 1-μm laser beam waist and a laser power at the sample of 40 mW.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Samples for Raman analysis were prepared by repeating the standard RT-QuIC protocol without the addition of ThT in order to avoid any signal interference. 31 A 5-μl drop of RT-QuIC product was deposited onto a gold mirror support (ME1S-M01; Thorlabs, Inc., Newton, NJ), followed by air drying for 20 minutes and acquisition of Raman spectra from the outer ring of the dried drop. A fitting procedure provided a semiquantitative estimate of the secondary structure composition.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…3 Examples of oligomeric diversity include fibrillar and non-fibrillar oligomers, 4 as well as toxic and non-toxic species. 5 A number of studies have demonstrated that oligomeric species are more toxic than fibrillar conformations both in vitro 3,6 and in vivo [7][8] . The binding of conformationally dependant antibodies to a range of toxic protein oligomers suggests that toxicity is directly associated with protein conformation, 9 with toxic oligomeric species being rich in β-sheet secondary structure 6,10 and displaying an increase in hydrophobic residue exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic and nontoxic forms of α‐synuclein oligomers were also found to differently expose hydrophobic regions, in particular a N‐terminus that is required to anchor the toxic species to the membrane, and a β‐sheet structure core that inserts into the membrane . Fluorescence data obtained with ANS, site‐directed labeling with different fluorophores and fluorescence resonance energy transfer (FRET) measurements pointed out to a connection between the toxicity of type A HypF‐N oligomers and the higher solvent‐exposure of three main hydrophobic regions, which encompass 18–30, 55–65, and 75–87 residues . Interestingly, the aromatic residues as well as one of the two His residues (His64) of the HypF‐N molecule are wholly located in these regions (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%